Understanding Electronic-commerce platforms' Role in Indirect Patent Infringement: Law Enforcers in the United States and Notice Enforcers in China (Global Journal of Human-Social Science, 2022)
More and more bad faith complaints about indirect patent infringement are filed to e-commerce platforms in China. The roles that e-commerce platforms play in indirect patent infringement are different, law enforcers in the United States and notice enforcers in China. In the context of indirect patent infringement, the e-commerce platform operators can take down the allegedly infringing listings only if the right holder can provide the court order enjoining the sales of the patented items. In contrast, the platforms in China seem to remove the allegedly infringing products when they receive the notice from the patentee. This paper examines IP policies between eBay and Alibaba, the largest e-commerce platforms in the U.S. and China, respectively. It also compares cases and statutes on the issue of indirect patent infringement occurring on e-commerce platforms to explore the different roles of e-commerce platforms in China and the US. Learning from the United States, the paper concludes with legislative and collaborative governance suggestions to pave the way for e-commerce platform governance in the context of indirect patent infringement.
Keywords: e-commerce platforms; indirect patent infringement; law enforcer; notice enforcer; notice and takedown rule